Genomic dissection of the microevolution of Australian epidemic Bordetella pertussis. Issue 1 (31st December 2022) - Xu, Zheng; Hu, Dalong; Luu, Laurence Don Wai; Octavia, Sophie; Keil, Anthony D.; Sintchenko, Vitali; Tanaka, Mark M.; Mooi, Frits R.; Robson, Jenny; Lan, Ruiting
ABSTRACT : Whooping cough (pertussis) is a highly contagious respiratory disease caused by the bacterium Bordetella pertussis. Despite high vaccine coverage, pertussis has re-emerged in many countries including Australia and caused two large epidemics in Australia since 2007. Here, we undertook a genomic and phylogeographic study of 385 Australian B. pertussis isolates collected from 2008 to 2017. The Australian B. pertussis population was found to be composed of mostly ptxP3 strains carrying different fim3 alleles, with ptxP3-fim3A genotype expanding far more than ptxP3-fim3B. Within the former, there were six co-circulating epidemic lineages (EL1 to EL6). The multiple ELs emerged, expanded, and then declined at different time points over the two epidemics. In population genetics terms, both hard and soft selective sweeps through vaccine selection pressures have determined the population dynamics of Australian B. pertussis. Relative risk estimation suggests that once a new B. pertussis lineage emerged, it was more likely to spread locally within the first 1.5 years. However, after 1.5 years, any new lineage was likely to expand to a wider region. Phylogenetic analysis revealed the expansion of ptxP3 strains was also associated with replacement of the type III secretion system allele bscI1 with bscI3 . bscI3 is associated with decreased T3SS secretion and may allow B. pertussis to reduce immune recognition. This study advanced our understanding of the epidemic population structure and spatial and temporal dynamics of B. pertussis in a highly immunized population.